2000
DOI: 10.1212/wnl.54.4.950
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and clinical analyses of spinocerebellar ataxia type 8 in Japan

Abstract: The CTG repeat expansions in the SCA8 alleles were much greater than the range of repeats in normal elderly subjects. The SCA8 phenotype manifested by cerebellar symptoms and atrophy corresponded to features of the autosomal dominant cerebellar ataxia type III (ADCA III).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
38
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 24 publications
2
38
0
Order By: Relevance
“…Ataxic dysarthria with limb and gait ataxia are the usual neurological findings but spasticity and diminished vibration perception have also been recorded. Neuropsychological or psychiatric deficits were not noted in the first two reports [1,2], but mild to moderate memory impairment was present in two of the seven patients reported by Silveira et al [3]. The paediatric patient had mental retardation.…”
mentioning
confidence: 81%
See 4 more Smart Citations
“…Ataxic dysarthria with limb and gait ataxia are the usual neurological findings but spasticity and diminished vibration perception have also been recorded. Neuropsychological or psychiatric deficits were not noted in the first two reports [1,2], but mild to moderate memory impairment was present in two of the seven patients reported by Silveira et al [3]. The paediatric patient had mental retardation.…”
mentioning
confidence: 81%
“…Sirs: A new form of autosomal dominant spinocerebellar ataxia (SCA8) with incomplete penetrance due to a non-coding expansion of CTG repeats on chromosome 13q21 has been described in seven kindreds in the United States [1], in a series of six patients from Japan [2] and seven from Portugal [3]. Further studies have reported a number of healthy controls and elderly unaffected family members who do not have ataxia but nevertheless have large expansions at the gene locus [3][4][5][6][7].…”
mentioning
confidence: 99%
See 3 more Smart Citations